2021
DOI: 10.1016/j.rbms.2020.10.004
|View full text |Cite
|
Sign up to set email alerts
|

The marketing of elective egg freezing: A content, cost and quality analysis of UK fertility clinic websites

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…Virtually any fertility clinic can claim that they can freeze women's oocytes for a couple of thousands of euros. There is very little legal regulation of the egg freezing practice (Gürtin and Tiemann, 2021). In our opinion, laboratories ought to be subject to audits to control their quality standards and to check their procedures and results, and caution is needed to prevent laboratories with low oocyte survival rates and poor success rates from advertising themselves while their "clients" may be unaware of the poor performance.…”
Section: Lack Of Control On Laboratories With Suboptimal Results and ...mentioning
confidence: 99%
“…Virtually any fertility clinic can claim that they can freeze women's oocytes for a couple of thousands of euros. There is very little legal regulation of the egg freezing practice (Gürtin and Tiemann, 2021). In our opinion, laboratories ought to be subject to audits to control their quality standards and to check their procedures and results, and caution is needed to prevent laboratories with low oocyte survival rates and poor success rates from advertising themselves while their "clients" may be unaware of the poor performance.…”
Section: Lack Of Control On Laboratories With Suboptimal Results and ...mentioning
confidence: 99%
“…This process added decision stress for some participants because of the administrative burden, a burden that could easily be avoided if clear information could be provided—for example, on clinic websites or during consultations. Other studies have also indicated it is particularly worrying that pricing information is usually unclear [ 46 , 47 ]. Greater transparency and in particular standardised presentation of reimbursement options could remedy that.…”
Section: Discussionmentioning
confidence: 99%
“…This process added decision stress for some participants because of the administrative burden, a burden that could easily be avoided if clear information could be provided -for example, on clinic websites or during consultations. Other studies have also indicated it is particularly worrying that pricing information is usually unclear [36,37]. Greater transparency and in particular standardised presentation of reimbursement options could remedy that.…”
Section: Discussionmentioning
confidence: 99%